ACTR-14. PHASE I STUDY OF AZD1775 WITH RADIATION THERAPY (RT) AND TEMOZOLOMIDE (TMZ) IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA (GBM) AND EVALUATION OF INTRATUMORAL DRUG DISTRIBUTION (IDD) IN PATIENTS WITH RECURRENT GBM. (5th November 2018) - Alexander, Brian; Supko, Jeffrey; Agar, Nathalie; Ahluwalia, Manmeet; Desai, Arati; Dietrich, Jorg; Kaley, Thomas; Peereboom, David; Takebe, Naoko; Desideri, Serena; Fisher, Joy; Sims, Megan; et al.
Abstract: AZD1775 is an oral small molecular inhibitor of the G2/M checkpoint regulator Wee1. The Adult Brain Tumor Consortium 1202 trial (NCT01849146) is a phase I, open label, multicenter dose-finding study of AZD1775 in combination with standard RT and TMZ followed by an IDD study for patients undergoing surgery for recurrent GBM. Dose of AZD1775 was increased in a 3 + 3 design M-F during concurrent RT/TMZ and x 5d/28d cycle with adjuvant TMZ in separate cohorts. A combination cohort with both concurrent and adjuvant AZD1775 at MTD and analysis of PK/PD and IDD at MTD in patients undergoing surgery for recurrent GBM followed. MTD was 200 mg for concurrent with 2/6 patients experiencing DLTs (grade 4 neutropenia, grade 3 ALT elevation). MTD for the adjuvant cohort was 425 mg with 1/6 patients experiencing DLT (grade 4 decrease in ANC). 6/12 patients experienced DLTs when cohorts were combined, however, five during the concurrent phase. Three patients had grade ≥3 ALT/AST elevation, one had grade 3 afib, and one had grade 4 neutropenia/thrombocytopenia, grade 3 dehydration/fatigue/muscle weakness. A sixth patient had grade 4 neutropenia in the first adjuvant cycle. Following amendment, an additional 6 patients were enrolled with 150 mg (concurrent) and 425 mg (adjuvant) combination and are in the observation period with one DLT currently. Drug concentration in contrast enhancing and non-enhancing brain tumor was 4–8 x and 0.5–2.6 x greater than plasma, respectively for patients on IDD portion. CONCLUSIONS: AZD1775 in combination with RT/TMZ at 200 mg qd M-F with concurrent RT/TMZ and 425 mg qd x 5d/28d cycle in combination with adjuvant TMZ had unacceptable DLT rate in the concurrent phase. A cohort with 150 mg concurrent/425 mg adjuvant has competed accrual with acceptable rates of toxicity currently in observation. AZD1775 has good penetration to non-enhancing and enhancing tumor areas.